The Effect Of Food Inflation, Per Capita Income and Consumer Spending On ASEAN Food Security - Ayuningtyas; Siti Nurjanah; Rd. Tuty Sariwulan (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of food inflation, per capita income, and consumer spending on food security in four ASEAN countries, namely Indonesia, Malaysia, Singapore, and Thailand, during the period 2013 to 2022. Using a quantitative approach with panel regression analysis, this study processed secondary data from various official sources, such as FAO, World Bank, and the Economist Intelligence Unit. The results of the study showed that independent variables, namely food inflation, per capita income and consumer spending, were able to explain the dependent variable, namely food security by 74%, while the remaining 25.3% was explained by other variables outside the model. This research provides important implications for policymakers in ASEAN countries in formulating strategies that can stabilize food prices, improve economic welfare, and optimize food distribution and accessibility to achieve more sustainable food security in the region.